Evaluation of Angiogenic Factors (PlGF and sFlt-1) in Pre-eclampsia Diagnosis - Catherine Primo Nogueira de Sá; Mirela Foresti Jiménez; Marcos Wengrover Rosa; Ellen Machado Arlindo; Antonio Celso Koehler Ayub; Rodrigo Bernardes Cardoso; Régis Kreitchmann; Patrícia El Beitune (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Objective: Recent observations support the hypothesis that an imbalance between angiogenic factors has a fundamental role in the pathogenesis of pre-eclampsia and is responsible for the clinical manifestations of the disease. The goal of the present study was to evaluate the sensitivity, specificity, and the best accuracy level of Soluble fms-like tyrosine kinase-1 (sFlt-1), placental growth factor (PlGF), and sFlt-1/PlGF ratio in maternal serum and protein/creatinine ratio in urine sample to define the best cutoff point of these tests to discriminate between the patients with gestational hypertension and the patients with pre-eclampsia, to evaluate the possibility of using them as diagnostic methods. Methods: A prospective longitudinal study was performed, and blood samples were collected from 95 pregnant patients with hypertension to measure serum concentrations of biomarkers sFlt-1 and PlGF. Urine samples were collected for protein screening. Significance was set as p < 0.05. Results: The sFlt-1/PlGF ratio demonstrated a sensitivity of 57.5% and a specificity of 60% using 50.4 as a cutoff point. The test that showed the best accuracy in the diagnosis of pre-eclampsia was protein/creatinine ratio, with a sensitivity of 78.9% and a specificity of 70% using 0.4 as a cutoff point and showing an area under the receiver operating characteristic curve of 0.80 (p < 0.001). Conclusion: No studied laboratory test proved to be fairly accurate for the diagnosis of pre-eclampsia, except for the protein/creatinine ratio. The evidence is insufficient to recommend biomarkers sFlt-1 and PlGF to be used for the diagnosis of pre-eclampsia.